2019
DOI: 10.3390/mi10050288
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors and Theoretical Models for the Surface Topography in Diamond Turning Process: A Review

Abstract: In this work, the influencing factors and corresponding theoretical models for the surface topography in diamond turning process are reviewed. The surface profile on one tool feed is the elementary unit of surface topography. The influences coupled with the models of the duplication effect of the tool edge profile, material spring back, and plastic side flow are outlined in this part. In light of the surface profile on one tool feed and “trim principle”, the modeling methods of surface topography along the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…Its formation is dependent on the mechanical properties of the material, primarily the strength and ductility. While models that take into consideration the elastic recovery, chip thickness and swelling ratio have been formulated, most are still based on assumptions and not followed by experimental observations [67], [70]. Nonetheless, a mathematical model developed by Liu.…”
Section: Figurementioning
confidence: 99%
“…Its formation is dependent on the mechanical properties of the material, primarily the strength and ductility. While models that take into consideration the elastic recovery, chip thickness and swelling ratio have been formulated, most are still based on assumptions and not followed by experimental observations [67], [70]. Nonetheless, a mathematical model developed by Liu.…”
Section: Figurementioning
confidence: 99%
“…Recently, there has been a dramatic increase in the breadth of applications for ultraprecision machining using single-crystal diamond tools [6]-particularly in the fields of manufacturing optical or magnetic parts, such as magnetic discs, polygonal mirrors, copier drums, and different lens shapes. As a result, the technique has successfully been expanded to machining various soft materials, creating mirror-like surfaces with submicrometer geometrical precision using ultraprecision machining and a single-crystal diamond tool [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that surface quality from diamond turning is influenced by many factors such as machine vibration, chatter, tool wear, tool geometry, built-up edge, chip striking, and lubrication. Indeed, the surface roughness of the diamond turning machine parts plays a crucial role [6,7]. ere are several difficulties when studying the surface roughness of diamond turning parts.…”
Section: Introductionmentioning
confidence: 99%
“…He and Zong 16 described the mechanism of multi-frequency vibration on the optical performance of diamond-turned workpieces, and he used well-established two-step process technology to reduce the effect of vibration, which was experimentally proved to be highly effective. 17,18 Gao et al 19 investigated the relationship between the ripple errors of machined surfaces and oil source pressure fluctuations and demonstrated that an unsteady oil source pressure had a remarkable effect on the topography of a workpiece. Wei et al 20 theoretically and experimentally investigated the dynamic characteristics of air spindles and their effect on medium-frequency ripples in machined surface shapes.…”
Section: Introductionmentioning
confidence: 99%